Convalescent Plasma Therapy in First Four Critically Ill COVID-19 Patients in Kerala, India - Nisar Karekadavath; Shinas Babu Pullichola; E. Muhammed Afsal; Anitha S.P. Prabhu; Mansoor C. Abdulla; Shahul H. Ebrahim (Dr. Sulaiman Al Habib Medical Journal)
We describe the first four coronavirus disease 2019 (COVID-19) cases in Kerala—the Indian state that reported the first COVID-19 case on January 30, 2020—who developed acute respiratory distress syndrome despite lopinavir/ritonavir and methyl prednisolone treatment. All four patients received convalescent plasma therapy. All four patients showed clinical improvement in 24–48 h and were discharged from hospital after negative severe acute respiratory syndrome coronavirus 2 reverse transcription- polymerase chain reaction test results.